Masywna kalcyfikacja mięśniaków macicy jako przyczyna porażenia splotu krzyżowego – opis przypadku = Massive calcification of uterine fibroids as a cause of sacral plexus palsy - a case study - Wójcik, Gustaw; Pocztarska, Agata; Stawińska, Teresa (Journal of Education, Health and Sport, 2016)
Wójcik Gustaw, Pocztarska Agata, Stawińska Teresa. Masywna kalcyfikacja mięśniaków macicy jako przyczyna porażenia splotu krzyżowego – opis przypadku = Massive calcification of uterine fibroids as a cause of sacral plexus palsy - a case study. Journal of Education, Health and Sport. 2016;6(10):331-336. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.162889 http://ojs.ukw.edu.pl/index.php/johs/article/view/3950 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 20.10.2016. MASYWNA KALCYFIKACJA MIĘŚNIAKÓW MACICY JAKO PRZYCZYNA PORAŻENIA SPLOTU KRZYŻOWEGO – OPIS PRZYPADKU MASSIVE CALCIFICATION OF UTERINE FIBROIDS AS A CAUSE OF SACRAL PLEXUS PALSY - A CASE STUDY Wójcik Gustaw1,2, Pocztarska Agata1, Stawińska Teresa3 1 Państwowa Szkoła Wyższa im. Papieża Jana Pawła II w Białej Podlaskiej, Wydział Nauk o Zdrowiu i Nauk Społecznych 2 Uniwersytet Medyczny w Lublinie, Katedra Rehabilitacji, Fizjopterapii i Balneoterapii, Zakład Balneoterapii 3 Uniwersytet Medyczny w Lublinie, Katedra Rehabilitacji, Fizjoterapii i Balneoterapii, Zakład Rehabilitacji SŁOWA KLUCZOWE: kalcyfikacja miednicy, mięśniaki macicy, splot krzyżowy, tomografia komputerowa STRESZCZENIE Mięśniaki macicy są jednym z najbardziej powszechnych, występujących u kobiet nowotworów miednicy. Często guzom tym nie towarzyszą żadne objawy, a znajdywane są zupełnie przypadkowo podczas badań prowadzonych z innych wskazań. Celem pracy jest prezentacja przypadku, w którym w wyniku powstania mięśniaków macicy i odkładania się w nim związków wapnia doszło do powiększenia i stwardnienia narządu powodującego porażenie splotu krzyżowego. Pacjentka lat 57 zgłosiła się do poradni neurologicznej z powodu długotrwałych dolegliwości bólowych kręgosłupa w odcinku lędźwiowo-krzyżowym i bólem promieniującym do prawej kończyny dolnej. W wyniku przeprowadzonej diagnostyki obrazowej nie stwierdzono ewidentnych zmian strukturalnych w obrębie kręgosłupa, które mogłyby powodować zaburzenia funkcjonalne kończyn dolnych. Badanie TK uwidoczniło natomiast znacznych rozmiarów mięśniakowatą macicę. Powiększenie macicy w wyniku patologicznego rozrostu spowodowało zaburzenia stosunków anatomicznych w miednicy i ucisk jej na sąsiadujące z nią struktury, w tym splot krzyżowy. Interpretacja badań obrazowych mięśniaków nie stwarza problemów, jednak w przypadkach kiedy dochodzi do ich zwapnień, obraz zmienionego narządu znacznie odbiega od normy. Ma to istotne znaczenie zwłaszcza dla klinicystów, którzy powinni znać ich odmienny wygląd oraz możliwość interakcji zmienionego narządu z przylegającymi strukturami. KEY WORDS: pelvic calcification, uterine myoma, sacral plexus, computed tomography ABSTRACT Fibroids are one of the most common pelvic tumors in women. These tumors are often not accompanied by any symptoms and are found by chance during research for other indications. The aim of this work is to present the case in which the creation of uterine fibroids and deposition of calcium compounds in those led to an enlargement and callosity of the organ causing the sacral plexus paralysis. Patient, 57, was admitted to the neurological clinic because of long-term back pain in the lumbosacral segment and pain radiating to the right leg. As a result of diagnostic imaging, there were no obvious structural changes in the spine, which may have caused functional disorders of the lower limbs. A CT scan revealed significant size of fibroid uterus. Enlargement of the uterus as a result of abnormal growth caused disorders in the anatomy of pelvis and its pressure to neighboring structures, including sacral plexus. The interpretation of imaging studies of fibroids does not pose a problem, but in cases when it comes to their calcification, the image of the amended organ is far from the norm. This is important especially for clinicians who need to know their different appearance and the ability to interact with adjacent structures.